PENGUATAN MODEL PEMBELAJARAN TAHFIZH ALQUR’AN PADA DAYAH AR-RAUDHAH TAHFIZH AL-QUR’AN - Diauddin Diauddin; Fitriani Agustina (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
This study aims to analyze the Strengthening of the Tahfizh Al-Qur'an Learning Model at Dayah Ar Raudhah Tahfiz Al-Qur'an, Blang mangat District, Lhokseumawe City. The research subjects were the students of Dayah Ar Raudhah Tahfizh Al-Qur'an, Blang Mangat District, Lhokseumawe. The type of research used is qualitative. Data collection techniques were carried out through: Observation, interview and document study. Data analysis techniques were carried out by means of data reduction, data presentation, and drawing conclusions. The results obtained: (1) Application of the learning model Dayah Tahfizh Al-Qur'an Ar Raudhah Lhokseumawe using the Ottoman Turkish tahfizh model or known as the backward sequence model with a standard time of memorizing 30 juz for 20 months, (2) Actualization of the Dayah Tahfizh learning model Al-Qur'an Ar Raudhah Lhokseumawe was carried out in 3 stages, namely: a pre-tahfizh program for 6 months, memorizing with a predetermined Ottoman model, and an evaluation stage carried out in 2 stages, (3) Obstacles in applying the tahfizh learning model to Dayah Ar Raudhah Tahfizh Al-Qur'an Lhokseumawe. first, feeling difficult when starting to memorize the Qur'an, because memorizing the Qur'an from the last page of each juz and having to start from the beginning for the thalib who had previously memorized the Qur'an. Second, Cannot be sure or determine how many juz memorized because the system is round. Meanwhile, efforts to overcome obstacles are carried out by fostering talib discipline and collaborating with the talib guardians.